2020
DOI: 10.1039/d0an00037j
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of nonlabelled bovine serum albumin using photothermal optical phase shift detection with UV excitation

Abstract: Ultrasensitive detection of nonlabelled bovine serum albumin is performed in micro/nanofluidic chips using a photothermal optical phase shift (POPS) detection system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…6. 78 In contrast to the setup shown in Fig. 5, the excitation beam is switched from VIS to UV light to detect a wide range of molecules, including proteins, peptides, amino acids, and nucleic acids.…”
Section: Instrumentationmentioning
confidence: 99%
“…6. 78 In contrast to the setup shown in Fig. 5, the excitation beam is switched from VIS to UV light to detect a wide range of molecules, including proteins, peptides, amino acids, and nucleic acids.…”
Section: Instrumentationmentioning
confidence: 99%
“…The targets of POPS detection are all molecules which have optical absorption in UV/vis range. For example, ~30 protein molecules were detected by the UV-POPS detector as shown in Figure 3 b [ 66 ].…”
Section: Optical Detectionmentioning
confidence: 99%
“…( b ) Detection of non-labeled bovine serum albumin by POPS. The limit of detection was 50 nM (30 molecules) (adapted with permission from [ 66 ]. Copyright 2020 The Royal Society of Chemistry).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results demonstrated that the measurement of the BSA concentration could still be obtained from the drift of the spectral line under interference factors. Recently, the detection of the nonlabelled BSA using photothermal optical phase shift (POPS) detection with ultraviolet (UV) excitation as well as BSA detection by atmospheric pressure plasma jets in matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) has been addressed [35,36]. Therefore, the GMLPG demonstrated a great potential for biosensing due to the simple monitoring system, label-free, and comparable LOD.…”
mentioning
confidence: 99%